Comparison of coach-athlete perceptions on internal and external training loads in trained cyclists - Inoue, A.; Crivoi do Carmo, E.; de Souza Terra, B.; Ryker Moraes, B.; Lattari, E.; Borin, J. P. (European Journal of Sport Science, 2022)
The aim was to compare the rating of perceived exertion (RPE), duration and session-RPE (S-RPE) prescribed by the coaches to those perceived by the cyclists in training sessions. The classification of RPE, duration and S-RPE of 14 male road cycling and mountain biking athletes were compared with the planned values of five coaches. The results revealed no differences for average RPE (P = 0.586), duration (P = 0.717) and S-RPE (P = 0.738) between coaches and cyclists. When comparing the three categories of effort, the results of the intensity of training sessions designed to be easy were perceived as significantly harder by cyclists compared to coaches (3.0 [2.0] vs. 2.0 [0.0] a.u.; P = 0.013). In addition, the correlations between coaches and cyclists on RPE (r = 0.73), duration (r = 0.95) and S-RPE (r = 0.87) were large, almost perfect and very large (P < 0.0001) respectively. In conclusion, our results indicate a mismatch between coaches (prescription) and cyclists (perception) of easy RPE training sessions, where the cyclists perceived the session harder. However, the S-RPE can be used to prescribe and quantifying the internal training load of trained cyclists.